ANALISIS PELAKSANAAN PEMUNGUTAN RETRIBUSI PASAR CIK PUAN KOTA PEKANBARU - HARIYANTI, NURUL; YULIANI, FEBRI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Fee Collection ofMarketAnalysisCikPuanPekanbaruThis study aims todetermine the fee collection is lacking a clear implementation Cik Puan Market Pekanbaru,their contribution to the original income and obstacles faced in the implementation of marketfee collection and efforts to overcome these obstacles.This research is descriptive. The type of data used is primary data sourced from theofficials and officers who are directly addressing the implementation of market fee collectionCik Puan Pekanbaru and secondary data obtained from the literature relating to the title of thethesis. Techniques leverage the data was done by using observation / observation, interviews/ interviews and literature. After the data collected in the subsequent qualitative analysis.Based on the analysis that has been done can be concluded that the implementation of marketfee collection Cik Puan Pekanbaru is the authority and responsibility of the Department ofMarket Pekanbaru City and executed entirely by Cik Puan UPTD Market Pekanbaru No.regulatory regions. 6 In 2012 the collection system directly or ticket.Implementation of fee collection Cik Puan Pekanbaru City Market in the last threeyears running poorly and the achievement of the target is still not stable. Obstaclesencountered in the implementation of market fee collection Cik Puan Pekanbaru include lackof awareness required to pay a levy levy in the market, infrastructure and inadequate marketinfrastructure, and personnel to pick up the less strict in retribution.Keywords: Implementation, Marketfee collection,Traditional Market.